Clinical and Laboratory Features of COVID-19 in Patients With Comorbid Conditions - Akramova Iroda Abroldjanovna; Agzamova Makhmuda Nabiyevna (Academia Open, 2026)
General Background: Coronavirus disease 2019 (COVID-19) is a multisystem infectious disease with diverse clinical manifestations and outcomes, particularly among hospitalized patients. Specific Background: Individuals with chronic diseases frequently experience more complicated clinical courses during COVID-19 infection, requiring detailed clinical and laboratory assessment to understand disease progression. Knowledge Gap: Despite numerous investigations, uncertainty remains regarding which clinical and laboratory characteristics are associated with severe and critical forms of COVID-19 in patients with multiple underlying conditions. Aims: This study analyzed the clinical manifestations and laboratory characteristics of COVID-19 patients with comorbid conditions and identified indicators associated with severe disease progression. Results: A total of 182 hospitalized patients with moderate, severe, and critical COVID-19 were examined during 2021–2022 using comprehensive clinical, laboratory, and instrumental assessments. The majority presented with severe disease (80.8%). Coronary heart disease, hypertension, anemia, type 2 diabetes mellitus, and obesity were the most frequent accompanying conditions. Severe and critical cases were more common among elderly individuals and those with multiple concurrent disorders. Clinical manifestations included fever, cough, dyspnea, and weakness, frequently accompanied by bilateral or polysegmental pneumonia and respiratory failure. Laboratory findings showed leukocytosis, neutrophilia, lymphopenia, elevated erythrocyte sedimentation rate, increased C-reactive protein levels, hyperglycemia, and altered liver and renal function markers, particularly in critically ill patients. Novelty: The study provides integrated clinical and laboratory characterization of hospitalized COVID-19 patients with multiple concurrent diseases. Implications: Identification of these clinical and laboratory indicators supports early risk stratification, timely initiation of intensive treatment, and improved management of patients with severe COVID-19. Highlights: Elderly Hospitalized Individuals Frequently Present Severe or Critical Disease Stages. Respiratory Failure and Bilateral Pneumonia Appear Commonly in Advanced Clinical Cases. Systemic Inflammation Markers and Metabolic Abnormalities Increase in Critically Ill Groups. Keywords: COVID-19, Comorbidities, Laboratory Parameters, Pneumonia, Respiratory Failure.